Law, politics, and finance - Beck, Thorsten 1967- (World Bank E-Library Archive, 2001)
A country's legal origin, whether British, French, German, or Scandinavian, helps explain the development of its financial institutions today. Legal systems differ in their ability to facilitate private exchanges and to adapt to support new financial and commercial transactions. A country cannot change its legal origin, but it can (with considerable effort) reform its judicial system by emphasizing the rights of outside investors, by providing more certain and efficient contract enforcement, and by creating a legal system that adapts more readily to changing economic conditions